2018
DOI: 10.1002/slct.201800103
|View full text |Cite
|
Sign up to set email alerts
|

Novel Electro‐Spun Nanograined ZnO/Au Heterojunction Nanofibers and Their Ultrasensitive NO2 Gas Sensing Properties

Abstract: Novel nanograined ZnO/Au heterostructured nanofibers have been successfully prepared using two‐step process via electrospinning method followed by thermal oxidation and their surface bound NO2 sensing properties were analyzed. The ZnO/Au heterojunction nanofibers exhibited typical nanograined structure with 1D morphology consisting of two distinct lattice fringes with d spacing values of 0.14 ± 0.5 nm and 0.28 ± 0.5 nm corresponding to Au [111] and ZnO [101] respectively. Defects and surface bound properties w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…For example, one-dimensional (1D) nanowires, nanorods, nanotubes, nanober structures, twodimensional (2D) nanosheets, nanoakes have high surfaceto-volume ratio, leading to greater electron depletion. [67][68][69][70][71] This characteristic accelerates the surface reaction, reduces the operating temperature, and nally achieves gas-sensing at lowoperating temperatures. For instance, Xia et al synthesized nanorods with different diameters through a simple nanoseedassisted method.…”
Section: Surface Morphological Modicationmentioning
confidence: 99%
“…For example, one-dimensional (1D) nanowires, nanorods, nanotubes, nanober structures, twodimensional (2D) nanosheets, nanoakes have high surfaceto-volume ratio, leading to greater electron depletion. [67][68][69][70][71] This characteristic accelerates the surface reaction, reduces the operating temperature, and nally achieves gas-sensing at lowoperating temperatures. For instance, Xia et al synthesized nanorods with different diameters through a simple nanoseedassisted method.…”
Section: Surface Morphological Modicationmentioning
confidence: 99%
“…In addition, previous reports have revealed that decoration with noble metals (such as Au, Pt, Pd, etc.) on ZnO nanostructures is one effective way to dramatically improve the gas sensing performance due to their chemical and electrical sensitization . For example, Xiao et al.…”
Section: Introductionmentioning
confidence: 99%
“…The intense diffraction peaks detected at 2θ resembles to the respective lattice planes further correlated to the hexagonal wurtzite phase of pure ZnO as revealed in our previous report. 34 In the case of ZnO-GNI HNFs, along with the characteristic peaks of ZnO, the 2θ peaks detected at 38.33 and 44.12 were Please do not adjust margins Please do not adjust margins recognized to be fcc structure of Au with existing lattice plane of (111) and (200) (JCPDS # 01-1174). Diffraction peaks corresponding to gold nanoislands and absence of peak shifts for hexagonal ZnO suggest the decoration of gold nanoislands which further confirmed the existence of heterojunctions in ZnO-GNI HNFs.…”
Section: (A)mentioning
confidence: 99%
“…59 It is noteworthy that the enhanced sensitivity of ZnO-GNI nanofibers can be attributed to the nanograined structure having enormous active heterojunction sites to adsorb more NO2 molecules compared to the crystalline 1D ZnO-GNI nanorods. 34 Based on the intricate analysis, we have understood that 1D aligned ZnO-GNI hetero-junction nanofibers possess enhanced sensing behavior due to the directed electron transport properties, hetero-junctions and formation of surface adsorbed oxide species, band-bending and spill-over sensitization, which have been justified by performing operando PL and electrical measurements. The NBE emission with deep level defects observed under operational condition was found to be favoring the band bending process in the heterojunctions, which further aided in understanding the complex sensing mechanism in 1D aligned MOS heterojunction MOS nanofibers at reduced operating temperature.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%